HUMAN NATURE AND EDUCATIONAL GOALS IN THE PROPHETIC PEDAGOGIC - Arie Rakhmat Riyadi (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
Education develops as a human effort to take advantage of what is in the universe. The purpose of education is the same as human goals. Humans want all humans, including their offspring, to be good humans. In more detail, the objectives of Islamic education can be classified into four groups, namely goals related to the body/physical condition (ahdaf jismiyah), moral development (ahdaf akhlaqiyah), intellectual development (ahdaf fikriyah), and expertise (ahdaf maslakiyah). This paper is compiled based on the views of experts, especially in Islam who discuss educational goals based on a prophetic pedagogic perspective.Keywords: Human Nature; Educational Goals; Prophetic Pedagogic. AbstrakPendidikan pada dasarnya berkembang sebagai usaha manusia mengambil manfaat dari apa yang ada dalam alam semesta. Tujuan pendidikan sama dengan tujuan manusia. Manusia menginginkan semua manusia, termasuk anak keturunannya, menjadi manusia yang baik. Secara lebih terperinci, tujuan pendidikan Islam dapat diklasifikasikan ke dalam 4 kelompok, yaitu tujuan yang berkaitan dengan badan/ keadaan fisik (ahdaf jismiyah), pembinaan akhlak (ahdaf akhlaqiyah), pembinaan akal (ahdaf fikriyah), dan keahlian (ahdaf maslakiyah). Tulisan ini disusun berdasarkan pandangan para ahli khususnya dalam Islam yang membahas tujuan pendidikan berdasarkan pespektif pedagogik profetik.Kata Kunci: Hakikat Manusia; Tujuan Pendidikan; Pedagogic Profetik.